Communicative approach to developing intercultural competence of future specialists in the service sphere (German after English) - Okopna, Yana (My University, 2010)
The paper shows how to develop students` intercultural competence in professionally-based dialogical speech (German after English) by promoting their intercultural skills and cross-cultural awareness. The research provides theoretical substantia¬tion and practical elaboration of the methodology of training future specialists in the service sphere to use paralinguistic in German oral professional communication.
Keywords: діалогічне мовлення; електронні засоби; німецька мова на базі англійської; професійно орієнтоване навчання; сфера обслуговування; диалогическая речь; средства обучения; немецкий язык после английского; профессионально ориентированное обучение; сфера обслуживания; dialogical speech; computer means; German on the English Ground; science; perspective; attention; кафедра іноземних мов професійного спрямування